A avaliação diagnóstica da alfabetização norteando os caminhos para o êxito do processo de alfabetizar crianças. - Ribeiro, Ana Paula de Medeiros (2011)
Nowadays, reaching quality in education is a target that cannot be separated of any kind of assessment procedures. The type, the frequency and the conditions of those assessments depend on their purpose in any situation. A diagnostic assessment can provide a previous knowledge about a class of students, making easier the pedagogical plans to a certain period of school time. The main objective of this study was to investigate how the diagnostic assessment could contribute to the success in literacy process of children, as well as, to identify some intervening factors in this process. In Ceara, since 2007, the Literacy in Right Age Program (PAIC) has been practiced this kind of assessment, in which the researcher works as a specialist. During the professional experience in this program, some questions about the causes of the differences in results among some cities, schools and classes were asking for a further investigation. The standardized procedures on how to use the results of diagnostic assessment were not sufficient to guarantee that all classes and students had good individual results. So, probably, there were any other factors involved. The main hypothesis of this study said that the diagnostic assessment contributes to the increase of learning when people involved in such process develop positive attitudes in relation of this practice and the actions that occur after it. Therefore, some factors linked to the individuals’ attitudes could influence more than socioeconomic factors. The study took place in two cities of Ceara, which involved 72 students and 4 teachers of two private schools, but having equivalent profile with the students and teachers of PAIC, which guaranteed the applicability of the study. The tests applied to the 72 students were the same applied by the Program. The results of students learning performance were registered, analyzed and presented not only in quantitative dimension, but also in a pedagogic one that helped in the comprehension of students’ development. Besides of this analysis, this study investigated, through the individuals’ speeches, the possible factors which would be causing influence in learning process. In this part, the hermeneutic method was used. This study presented as the main results: (1) It was possible to identify the learning development in reading and writing skills, because the appliance of a diagnostic assessment in May, 2009 and a comparative one in November, 2009; (2) The students showed a qualitative development of their performance; (3) The students from a lower socioeconomic level in one of the three investigated classes had better results. In the other two classes, the students’ results were very similar; (4) Some subjective aspects of the teachers and parents appeared as factors that contributed to a better learning process. They were: will, commitment, acceptance and praxis; (5) Monitoring activities which involve supervision and teachers’ continuing formation is essential to the quality of the pedagogic actions. This study found evidences that the diagnostic assessment can contribute meaningfully to guide the ways of the success in children literacy acquisition, when individuals involved into this process develop commitment to use the assessments’ results, plan and execute the pedagogic actions and monitoring didactic work.